2023
DOI: 10.3390/antibiotics12030619
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Drug Design and Synthesis of Rhenium Clotrimazole Antimicrobial Agents

Abstract: In the context of the global health issue caused by the growing occurrence of antimicrobial resistance (AMR), the need for novel antimicrobial agents is becoming alarming. Inorganic and organometallic complexes represent a relatively untapped source of antibiotics. Here, we report a computer-aided drug design (CADD) based on a ‘scaffold-hopping’ approach for the synthesis and antibacterial evaluation of fac-Re(I) tricarbonyl complexes bearing clotrimazole (ctz) as a monodentate ligand. The prepared molecules w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 85 publications
(97 reference statements)
1
8
0
Order By: Relevance
“…Besides that, very recently, the crystal structure of fac -tricarbonylrhenium( i ) complex bearing two different ligands, monodentate clotrimazole and bidentate 2,2′-bipyridine, has been reported. 26 Complexes 1 and 3 show relatively simple structures, both containing two monodentately N3-coordinated azole ligands (econazole and clotrimazole, respectively) forming a complex cation with linear geometry as expected (Fig. 1).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Besides that, very recently, the crystal structure of fac -tricarbonylrhenium( i ) complex bearing two different ligands, monodentate clotrimazole and bidentate 2,2′-bipyridine, has been reported. 26 Complexes 1 and 3 show relatively simple structures, both containing two monodentately N3-coordinated azole ligands (econazole and clotrimazole, respectively) forming a complex cation with linear geometry as expected (Fig. 1).…”
Section: Resultssupporting
confidence: 60%
“…S3–S5†) and their assignment was performed based on the NMR data reported in the literature for the studied azoles, whose 1 H NMR spectra were recorded in different solvents. 24,26,35 As can be seen in Fig. S3–S5,† most of the 1 H resonances for the coordinated azoles are downfield shifted concerning those for the uncoordinated ligand.…”
Section: Resultsmentioning
confidence: 84%
“…The antifungal clotrimazole (Clo) has been utilised as a ligand in several other studies and found to convey some level of biological activity that goes beyond the activity of the parent compound. 17,22,45 We have hence included it in our studies as a means to compare our compounds to others reported in the literature.…”
Section: Optimization Of Mnco 3 Combinatorial Synthesis and Preparati...mentioning
confidence: 99%
“…However, their targets and mechanism of action need further research. [3][4][5] Microbial metabolites are the source of many existing antibiotics and other medicines. For their high diversity and broad bioactivity spectra, short peptides are among the most widely studied secondary metabolites, and the large group of antimicrobial peptides (AMPs) produced by bacteria has been used to treat bacterial, fungal, and viral infections and even cancer.…”
Section: Motivationmentioning
confidence: 99%